Recipient Vessel Thrombectomy and Anastomosis within the Zone of Injury in Microvascular Extremity Reconstruction - Powers, Jeremy M.; Choi, Jaime H.; Kale, Santosh S. (Journal of Reconstructive Microsurgery Open, 2020)
Background In traumatic extremity reconstruction, it is preferable to perform microvascular anastomoses outside the zone of injury. Alternatively, a recipient-vessel thrombectomy can be performed to improve the arterial inflow, potentially avoiding further proximal dissection and the use of a vein graft. The objective of this study was to evaluate the outcomes of microvascular anastomosis after thrombectomy in the zone of injury.Methods A retrospective review of patients who underwent free tissue transfer for traumatic extremity reconstruction by the senior author from 2013 to 2017 was conducted. Patient demographic and clinical data were gathered as well as use of vein grafts, recipient-vessel thrombectomy, postoperative anticoagulation, and flap outcomes.Results A total of 23 patients underwent 24 free flap procedures for traumatic extremity reconstruction. Ten patients underwent recipient-vessel thrombectomy with 2-Fr Fogarty catheter and were placed on postoperative anticoagulation. In this group overall, there was one case of flap loss due to late wound infection resulting in a 90% success rate. A total of 13 patients underwent 14 free flaps without the use of thrombectomy and vein grafts were performed for 3/14 (21%) patients. In this group, there were four cases of flap loss, resulting in a 71% overall success rate.Conclusion In traumatic extremity reconstruction, if the artery appears to be visibly appropriate with weak inflow, one may consider attempting thrombectomy to restore pulsatile flow prior to harvesting a vein graft. This study suggests this may be effective and safe with no anastomosis-related flap loss in the thrombectomy group. Further research is required to confirm our results.
Keywords: lower extremity reconstruction; microvascular reconstruction; zone of injury; thrombectomy; vessel preparation